Digest: Structuring interactions in Streptomyces. (10th December 2019) - Singhal, Sonia
Abstract: For bacteria growing in colonies, spatial structure can allow maintenance of costly traits such as the production of antibiotics. Using spatially structured environments, Westhoff et al. examined the benefits of streptomycin production for the bacterium Streptomyces griseus in competition with a streptomycin‐susceptible strain. Streptomyces griseus outcompeted susceptible competitors, but the benefit of its antibiotic decreased as competitor resistance to streptomycin increased. Spatial structure also increased the ability of S. griseus to invade susceptible competitor populations from low starting densities. These results demonstrate that spatially structured environments can both provide and amplify benefits of antibiotics to antibiotic‐producing bacteria on a microbial scale.